Nano-targeting of mucosal addressin cell adhesion molecule-1 identifies bowel inflammation foci in murine model. (July 2017) - Truffi, Marta; Colombo, Miriam; Peñaranda-Avila, Jesus; Sorrentino, Luca; Colombo, Francesco; Monieri, Matteo; Collico, Veronica; Zerbi, Pietro; Longhi, Erika; Allevi, Raffaele; Prosperi, Davide; Corsi, Fabio
Aim: We investigate MAdCAM-1 as a reliable target to detect active bowel inflammation for selective noninvasive nanodiagnostics.Materials & methods: We coupled anti-MAdCAM-1 antibodies to manganese oxide nanoparticles, and analyzed nanoconjugate biodistribution and safety in murine model of inflammatory bowel disease by imaging and histology.Results: Nanoparticles were stable and nontoxic. Upon administration in colitic mice, anti-MAdCAM-1 functionalized nanoparticles preferentially localized in the inflamed bowel, whereas untargeted nanoparticles were more rapidly washed out. Nanoparticles did not induce lesions in nontarget organs.Conclusion: Anti-MAdCAM-1 functionalized nanoparticles detected active bowel inflammation foci, accurately following MAdCAM-1 expression pattern. These nanoconjugates could be a promising noninvasive imaging system for an early and accurate follow-up in patients affected by acute colitis.